Akabane virus isolated from biting midges and its infection in local domestic animal, Yunnan, China: a field and laboratory investigation - Meng, Jinxin; He, Yuwen; Li, Nan; Yang, Zhenxing; Fu, Si; Wang, Dongmei; Xin, Aiguo; Wang, Jinglin; Liang, Guodong (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionWe verified that Akabane virus (AKAV) is transmitted through biting midges and infects local domestic animals.MethodsIn 2013, viruses were isolate from biting midges in Yunnan, China, using BHK-21 and C6/36 cells. Two AKAV strains (No. 52 and 55) that induced cytopathogenic effects (CPE) in BHK-21, MDBK, and Vero cells were characterized.ResultsThe complete genomic sequence of both viruses consisted three RNA segments (S, M, and L). The S segment (856 nucleotides) encoded a 233-amino-acid nucleocapsid protein and a 91-amino-acid nonstructural protein, while the M segment (4309 nucleotides) encoded a 1401-amino-acid polyprotein. The L segment (6869 nucleotides) encoded a 2511-amino-acid RNA-dependent RNA polymerase. Phylogenetic analysis revealed that specimen Nos. 52 and 55 clustered with AKAV genotype Ia viruses isolated from Asia. The AKAV strain (55) neutralizing antibody exhibited a total positive rate of 43.55% (202/466) against serum samples from cattle and goats collected in Yunnan Province. Specifically, the positive rates were 48.77% (139/285) for cattle and 34.81% (63/181) for goats. Neutralizing antibody titers in cattle (1:32–1:128) were higher than those in goats (1:4–1:16).DiscussionThis study represents the first isolation of AKAV from biting midges in China, along with the detection of high neutralizing antibody titers against AKAV in the serum samples of local cattle and goats. These findings suggested that biting midges are involved in AKAV transmission among domestic animals in Yunnan Province, China.